Institutional logics in action - Lounsbury, Michael; Boxenbaum, Eva (Research in the sociology of organizations ;, 2013)
The institutional logics perspective is one of the fastest growing new theoretical areas in organization studies (Thornton, Ocasio & Lounsbury, 2012). Building on early efforts by Friedland & Alford (1991) to "bring society back in" to the study of organizational dynamics, this new scholarly domain has revived institutional analysis by embracing a focus on the dynamic and heterogeneous nature of institutions. In doing so, it has embraced a more practice-centered approach to agency that emphasizes situated interactions, the importance of history, the role of both symbolic and material elements, and the study of cross-level processes and mechanisms. This two volume set, seededby an ABC Network conference held in Banff, Alberta, CANADA in June 2012, provides a fresh set of papers by scholars at the cutting edge of research on institutional logics. As a whole, the papers provide many novel theoretical insights about institutional logics in actionfocusing on their dynamics, complexity, and evolving relationship to actors as actors actively navigate their social worlds.